55Monitoring the levels of the reactive oxygen species and calcium in the whole beating heart during ischaemia-reperfusion. (15th July 2014) - Andrienko, TN; Pasdois, P; Halestrap, AP
Abstract: The mitochondrial permeability transition pore (MPTP) plays a key role in reperfusion injury, and preventing MPTP opening is cardioprotective. Here we use surface fluorescence of a Langendorff-perfused beating rat heart to establish the role of ROS and [Ca2+] during ischemia and reperfusion in mediating MPTP opening. We used real-time multi-wavelength measurements of surface fluorescence and reflectance to monitor autofluorescence and intracellular concentrations of both [Ca2+] and ROS using Indo-1 and 5-carboxy-2′, 7′-dichlorofluorescein. Haemodynamic function and infarct size were measured in parallel. Increases in both ROS and [Ca2+] were detected on reperfusion and these were greatly attenuated by ischaemic preconditioning (Table 1) which reduced infarct size from 61.9±2.3% to 13.9±1.7% for IP. However, the time courses of the changes suggested that the increases in both parameters were secondary to MPTP opening rather acting as a causative event that than preceding MPTP opening. This conclusion received additional support from the observation that the MPTP inhibitor, cyclosporine A (0.2 μM CsA added 10 min before ischaemia and for 30 min of reperfusion), also reduced the rise in [Ca2+] upon reperfusion and decreased infarct size to 44.1±3.9%. Our data suggest that the observed changes in ROS and [Ca2+] during reperfusion may occur as a result of MPTP opening rather than acting as the trigger MPTP opening. We suggest that other factors such as hexokinase 2 dissociation from the mitochondria during ischemia may sensitize the MPTP to open at basal levels of [Ca2+] and ROS. Upon MPTP opening, the resulting mitochondrial dysfunction leads to ROS production, impaired ATP production and hence loss of calcium homeostasis that in turn leads to further MPTP opening and damage. This work was supported by the Medical Research Council and British Heart Foundation. Table 1 Indo-1 ratio DCF, normalized per value at 1 min on reperfusion Control (n = 15) IP (n = 10) CsA (n = 8) Control (n=6) IP (N = 6) normoxia 0.63±0.01 0.58±0.01 0.61±0.01 1.16±0.03 1.10±0.05 end of isch 0.79±0.02 0.80±0.02 0.85±0.04 3 min of rep 0.67±0.03 0.50±0.01* 0.55±0.02* 1.01±0.02 0.97±0.01 § 10 min of rep 0.87±0.10 0.53±0.02* 0.59±0.02* 1.10±0.03 0.95±0.01 § 30 min of rep 0.85±0.06 0.55±0.02* 0.59±0.03* 1.27±0.03 1.04±0.02 § *, § indicates significant difference to control